The influence of macrocultural change on national governing bodies in British Olympic sports - Feddersen, N. B.; Morris, R.; Abrahamsen, F. E.; Littlewood, M. A.; Richardson, D. J. (Sport in Society: Cultures, Commerce, Media, Politics, 2021)
The study objective was to examine the temporal macrocultural changes in Olympic sports in the United Kingdom and what regulates these changes. We carried out this study integrating grounded theory and action research in a 16-month longitudinal design. We collected data from eighteen interviews with participants from governing sports organisations (n = 6; GSOs) and NGBs (n = 3). Supplementary data came from ethnography with one national governing body; ten focus-groups with athletes, coaches, parents, and NGB personnel; and eight interviews with stakeholders. We found that political will had shielded Olympic sports from societal changes. However, macrocultural changes to social standards and the power of athletes highlighted that the organisational culture was increasingly deficient and required radical changes. GSOs used their systemic power to dictate appropriate avenues for change. Athletes used their reinforced position by speaking out about aspects that challenged the welfare of athletes and others working in Olympic sports.